Pengalaman Buruk Berolahraga dan Kegiatan Fisik Siswi SMP di Kutai Barat - Yudha, Gilbert Singo; Aswara, Agung Yuda (SPRINTER: Jurnal Ilmu Olahraga, 2025)
There is strong evidence that the level of public health in Indonesia is decreasing. Therefore, good physical activity needs to be done. This study aims to produce information about the bad experiences of sports participation and physical activity of junior high school students in West Kutai. This study uses a comparative correlational approach, secondary data obtained from the center of educational sports studies, master's degree in sports education, Insan Budi Utomo University, Malang. The population is all junior high schools in West Kutai, respondents 377 female students, namely 112 junior high school students and 265 MTs students. The results of data analysis: the average bad experience is 20.8 greater than the criterion of 18.2, the average physical activity is 20.85 smaller than the criterion of 23.9, the difference in bad experiences based on school type Sig. value. (2-tailed) is 0.317 greater than α 0.05, the difference in physical activity based on school type Sig. value. (2-tailed) is 0.026 smaller than α 0.05, the correlation coefficient of bad experiences with physical activity is 0.017. Conclusion: Junior high school students in West Kutai do not meet the tolerance threshold set for the bad experience variable and do not meet the good standards for the physical activity variable, there is no difference in bad experiences based on school type, there is a difference in physical activity based on school type, there is no relationship between bad experiences and physical activity.